SENSITIVITAS MEDIA OGAWA DAN MEDIA LOWENSTEIN JENSEN TERHADAP HASIL PERTUMBUHAN KUMAN MYCOBACTERIUM TUBERCULOSIS - Pancawati Ariami; Maruni Wiwin Diarti; Yunan Jiwintarum (Jurnal Kesehatan Prima, 2014)
Abstract: Referring to the national TB control program, the diagnosis made by microscopic examination of sputum by direct and definitive diagnosis by culture examination. Direct sputum examination is the gold standard method of microscopic examination of a recognized WHO TB and confirmation done by the method of culture. Research "Sensitivity Test Using Ogawa Medium and Lowenstein Jensen Medium Againts Micobacterium tuberculosis Bacteria Growth Results ", performed to identify and compare the results of Ogawa medium and culture on Lowenstein-Jensen medium and analyze the sensitivity between the two medium. A descriptive observational study was conducted. Study sample is a sample saturated with a consecutive sampling. Sample size retrieval technique based on sample collection time, which is June 8 through July 18, 2011, a total of 53 samples. Research is to test the sensitivity variables as independent variables and the growth of Mycobacterium tuberculosis bacteria on the Ogawa medium and LJ medium as a bound variable. The results of the study, of 53 samples, 21 (39.6%) samples were negative, so that 32 (60.4%) samples tested positive for M tuberculosis and the total growth of 36 samples (67.9%). Lowenstein Jensen (LJ) medium is more sensitive than the Ogawa medium, both in terms of speed of growth and in the number of colonies that grow. For the determination of Mycobacterium species needs to be done other tests to confirm. Culture results can also be used for comparison using the PCR method, OAT resistance by culture methods.